Powstanie 1863-1865. Nieznani bohaterowie, nieznane wydarzenia - GOSK, Milena (Historia i Świat, 2013)
The Uprising 1863-1865. Unknown heroes, unknown event - The work was awarded the first prize in the competition commemorating "the 150th anniversary of the January Uprising" announced by the Institute of History and International Relations of the University of Natural Sciences and Humanities in Siedlce.